Evaluation of the Implementation of the ASIK Program (a Health Application in Indonesia) for Child Immunization Report in the Ngoro Mojokerto Public Health Center - Nabilah Amirah Filda Rahmania; Cholifah Cholifah; Umi Khoirun Nisak (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The evaluation implementation in this application aims to trial the ASIK Application program (a Health Application in Indonesia), one of which is an achievement from the Indonesian Ministry of Health on National Child Immunization (BIAN) 2022. The purpose of the research is to find out the results of implementing the use of the ASIK application in inputting and monitoring data on the development of patients or program participants for all health workers who are applied to immunization at the puskesmas. The method used in this study was quantitative. The samples were all users of ASIK application in the Ngoro Public Health Center, with 102 respondents. Data analysis used simple linear regression analysis. The results obtained are five heuristic components, but the results that significantly influence variables with a significance value of <0.05 are the Consistency and Standard components with a result of 0.0001. It can be concluded that the ASIK application is beneficial in work, but it still influences the application, which should be reassessed immediately